2015
DOI: 10.1021/es5059378
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Production Mediated by Humic-like Substances in Atmospheric Aerosols: Enhancement Effects by Pyridine, Imidazole, and Their Derivatives

Abstract: 13Ambient particulate matter (PM) can cause adverse health effects via their ability to produce

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
117
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 43 publications
5
117
1
Order By: Relevance
“…S9). Dou et al (2015) showed that by forming H-bonds with hydroquinones, imidazole derivatives are capable of facilitating electron transfer from hydroquinones to molecular oxygen, accelerating the redox cycling of quinones and enhancing the oxidation of DTT (Scheme S4). In the DTT enhancement test, a 250 µL 2,4-dimethylimidazole aqueous solution (5 mM) was mixed with a 450 µL SOA PILS sample to get a 700 µL mixture.…”
Section: Pan Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…S9). Dou et al (2015) showed that by forming H-bonds with hydroquinones, imidazole derivatives are capable of facilitating electron transfer from hydroquinones to molecular oxygen, accelerating the redox cycling of quinones and enhancing the oxidation of DTT (Scheme S4). In the DTT enhancement test, a 250 µL 2,4-dimethylimidazole aqueous solution (5 mM) was mixed with a 450 µL SOA PILS sample to get a 700 µL mixture.…”
Section: Pan Analysismentioning
confidence: 99%
“…The amount of PAN was measured using the Griess assay and that of organic hydroperoxides was measured using the 4-nitrophenylboronic acid (NPBA) assay. The contribution of quinones to the oxidative potential of SOA was estimated by the enhancement of DTT consumption in the presence of 2,4-dimethylimidazole, a co-catalyst for the redox cycling of quinones (Dou et al, 2015). In addition to particulate oxidizers, the contribution of electron-deficient alkenes to DTT activity was investigated for aromatic SOA (toluene SOA).…”
Section: Introductionmentioning
confidence: 99%
“…At the global scale, the most recent estimates for the year 2000 (Lamarque et al, 2010) have shown that anthropogenic combustions and biomass burning roughly generate about 65 and 35 % of EC emissions, respectively, and 35 and 65 % of primary OC emissions. OC and EC not only contribute to the overall PM 2.5 load, but these components also have specific public health concerns because of their interactions with the human body (Dou et al, 2015;Shi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is mediated by reactive oxygen species (ROS), including OH, H 2 O 2 and superoxide (O − 2 ), as well as organic radicals (Pryor et al, 1995;Winterbourn, 2008;Birben et al, 2012;. Upon PM deposition into the respiratory tract and interactions with lung antioxidants, H 2 O 2 can be generated by redox-active components contained in PM 2.5 such as transition metals (Charrier et al, 2014;Fang et al, 2016), semiquinones (Kumagai et al, 1997;Cho et al, 2005;McWhinney et al, 2013) and humic-like substances (Kumagai et al, 1997;Cho et al, 2005;Lin and Yu, 2011;Charrier et al, 2014;Dou et al, 2015;Fang et al, 2016;Verma et al, 2015a). H 2 O 2 can be converted into highly reactive OH radicals via Fenton-like reactions with iron and copper ions (Charrier et al, 2014;Enami et al, 2014).…”
Section: Introductionmentioning
confidence: 99%